STAGING THE SELF: GENDER PERFORMATIVITY AND POSTMODERN FEMINISM IN MARINA DIAMANDIS’S MUSIC - Dr. Prasanna Deshpande (IJRDO Journal of Language, Gender and Literature studies, 2026)
This paper offers a critical analysis of select songs by Marina Diamandis—namely “Primadonna,” “How to Be a Heartbreaker,” and “Bubblegum Bitch”—through the theoretical lenses of Judith Butler’s gender performativity and postmodern feminist thought. It argues that Marina’s work exemplifies how popular culture functions as both a site of gender norm reproduction and a potential space of subversion. Drawing on Butler’s foundational claim that gender is not an innate identity but a series of socially compelled performative acts, the chapter explores how Marina’s ironic and self-aware lyrical strategies expose the constructed and unstable nature of femininity. It further integrates postmodern feminist critiques of identity fragmentation, consumer culture, and the rejection of essentialist notions of womanhood, as theorized by bell hooks, Teresa de Lauretis, and Fredric Jameson. The chapter demonstrates that Marina’s exaggerated personas do not offer coherent models of feminist identity but rather perform contradictory stances—simultaneously complicit with and critical of patriarchal and capitalist gender scripts. Through analysis of lyrics, visual aesthetics, and cultural positioning, the study reveals the complex interplay between performativity, hyperreality, and the commodification of femininity. Ultimately, it situates Marina’s music as a key site for understanding the politics of gender identity in contemporary popular culture.